(x*1.5*20)+(x*40)=600

Simple and best practice solution for (x*1.5*20)+(x*40)=600 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x*1.5*20)+(x*40)=600 equation:


Simplifying
(x * 1.5 * 20) + (x * 40) = 600

Reorder the terms for easier multiplication:
(1.5 * 20x) + (x * 40) = 600

Multiply 1.5 * 20
(30x) + (x * 40) = 600

Reorder the terms for easier multiplication:
(30x) + (40x) = 600

Combine like terms: (30x) + (40x) = 70x
70x = 600

Solving
70x = 600

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '70'.
x = 8.571428571

Simplifying
x = 8.571428571

See similar equations:

| 3s-9t=1 | | 6+6d=-6+10d | | b^4-2500b^2+1440000=0 | | -3(2x-2)=-2+3x | | b^2-2500b^2+1440000=0 | | -1+2g+2=6 | | -17.5+15y=10 | | 12+2n=7+2n+3 | | 34-x=57-42 | | 4x+n=100 | | 10x-4+5x+79=180 | | 9x-3=2x-15 | | 5q+10=-10+10q+5 | | 2(3k+58)=4(k+810) | | (4+5x)(4-5x)= | | 17x+2y=0 | | 4x+(4x-3)=37+3x | | 3(4z+900)=7(z+10100) | | (6x)(x+3)=0 | | 4(2p-8)-6=20+4(p+6) | | -6w+1=9-4w | | -10f+10=-12f | | -v=2v+9 | | s=120+71 | | x+(x*.15)=805 | | -7z-8=-8z | | -(8x-4)=-4x-3(x-3) | | 15.16+13.5k=-4.86+12.1k | | 15000/3= | | 7+2g=3g | | 15000%3= | | 11x-2y= |

Equations solver categories